1970
DOI: 10.1128/iai.1.4.387-393.1970
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and Characterization of a Protective Antigen of Erysipelothrix rhusiopathiae

Abstract: A particulate fraction of Erysipelothrix rhusiopathiae cultures has been subjected to butanol extraction and treatment with surface-active agents in an attempt to solubilize a protective antigen. The particulate fraction was partitioned into the butanol layer but was not solubilized. Only sodium dodecyl sulfate solubilized the particles. The soluble protective activity was not sedimented by centrifugation at 198,000 × g for 12 hr but was excluded by Sephadex G-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
1
9
2
Order By: Relevance
“…It has been reported that the protective antigen of E. rhusiopathiae is also present in the culture supernatant of the organism and that antiserum against the culture supernatant fluids is protective (8,9,15,16). Although we found that SpaA.1 is also present in the culture supernatant, we do not yet know the relationship between the bound SpaA.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…It has been reported that the protective antigen of E. rhusiopathiae is also present in the culture supernatant of the organism and that antiserum against the culture supernatant fluids is protective (8,9,15,16). Although we found that SpaA.1 is also present in the culture supernatant, we do not yet know the relationship between the bound SpaA.…”
Section: Discussioncontrasting
confidence: 74%
“…Although we found that SpaA.1 is also present in the culture supernatant, we do not yet know the relationship between the bound SpaA. the protective antigens found in the culture supernatant reported so far (8,9,15,16).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although protective antisera for passive immunization have been available for many years, the identity of the protective antigen(s) has not been clearly established. White and Verwey (28,29) described a large-molecular-weight protective antigen in culture supernatants; more recently, Lachmann and Deicher (12) have described smaller-molecular-weight antigenic components by immunoblotting.…”
mentioning
confidence: 99%
“…Already in 1970 a protective antigen was described from an E. rhusiopathiae culture (86). In 1990, a 64 to 66-kDa protein in cell wall extracts was shown to be protective (125).…”
Section: Protective Antigensmentioning
confidence: 99%